Conformational populations of ligand-sized molecules by replica exchange molecular dynamics and temperature reweighting - Okumura, Hisashi (2010)
The use of the replica exchange (RE) molecular dynamics (MD) method for the efficient estimation of conformational populations of ligand-sized molecules in solution is investigated. We compare the computational efficiency of the traditional constant temperature MD technique to that of the parallel RE molecular dynamics method for a series of alkanes and rilpivirine (TMC278), an inhibitor against HIV-1 reverse transcriptase, with implicit solvation. We show that conformational populations are accurately estimated by both methods, however replica exchange estimates converge at a faster rate especially for rilpivirine which is characterized by multiple stable states separated by high free energy barriers. Furthermore convergence is enhanced when the weighted histogram analysis method (WHAM) is employed to estimate populations from the data collected from multiple RE temperature replicas. For small drug-like molecules with energetic barriers separating the stable states, the use of RE with WHAM is an efficient computational approach for estimating the contribution of ligand conformational reorganization to binding affinities.